2019
DOI: 10.1002/anie.201908793
|View full text |Cite
|
Sign up to set email alerts
|

Pressure‐Induced Multiphoton Excited Fluorochromic Metal–Organic Frameworks for Improving MPEF Properties

Abstract: In multiphoton excited fluorescence (MPEF), highenergy upconversion emission is obtained from low-energy excitation by absorbance of two or more photons simultaneously.I napressure-induced fluorochromic process,t he emission energy is switched by outer pressure stimuli. Now,five metal-organic frameworks containing the same ligand with simultaneous multiphoton absorption and pressure-induced fluorochromic attributes were studied. One-, two-, and threephoton excited fluorescence (1/2/3PEF) can be achieved in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
44
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(45 citation statements)
references
References 53 publications
(8 reference statements)
1
44
0
Order By: Relevance
“…It is well known that generally zirconium‐based MOFs possess good structural stability . MOF‐808(Zr) as one member of them has received much attention due to its advantages such as high specific surface area (∼2000 m 2 /g), large pore opening, good stability and rich metal sites .…”
Section: Introductionmentioning
confidence: 99%
“…It is well known that generally zirconium‐based MOFs possess good structural stability . MOF‐808(Zr) as one member of them has received much attention due to its advantages such as high specific surface area (∼2000 m 2 /g), large pore opening, good stability and rich metal sites .…”
Section: Introductionmentioning
confidence: 99%
“…Zhang et al demonstrated the tunable optical limiting effect in the 3PA, both two-photon absorption (2PA) and 3PA can be found in Ni 3 HHTP 2 (d 8 ), and Cu 3 HHTP 2 (d 10 ) shows prominent 2PA. The 2PA cross-section of Cu 3 HHTP 2 is 1.38 ± 0.11 × 10 7 GM, much larger than those of reported NLO materials reported so far (e.g., 2217 GM for pressed LIFM-114, [33] 1.82 × 10 5 GM for CsPbBr 3 , [34] and 3.45 × 10 6 GM for Au 2406 [35] ). The band structure and the density of states (DOS) of M 3 HHTP 2 were derived from absorption spectra and valence band X-ray photoelectron spectroscopy (XPS) spectra, and it is found that the DOS of d band of metal atoms influences heavily the NLO response of M 3 HHTP 2 .…”
Section: Introductionmentioning
confidence: 61%
“…Recently, the first report on the NLO piezofluorochromism has been published by Pan and co-workers. [32] Five Zr-MOFs (LIFM-66, LIFM-114, LIFM-223, PCN-94, and PCN-128) comprising the same AIE-active TCPE linker, were subjected to compression by applying up to 1.5 tonnes load, using laboratory press. Comparison of 2PA action cross sections (780 nm excitation) measured before and after compression in each case showed www.advopticalmat.de gain, but its extent was widely different.…”
Section: Pressure-dependent 2pa In Aie Mofsmentioning
confidence: 99%